Mentoring trainee teachers in the voluntary and community sector: a case study in initial teacher training - Morris, Beverley (2010)
This thesis is a case study of a small number of Voluntary and Community Sector (VCS) education providers in the East of England. It focuses on their response to the introduction of mentoring for Initial Teacher Training (ITT) and aims to describe existing interpretations and practice, highlight confusion and concerns and offer insights into the next steps for both the VCS and providers of ITT courses in the wider sector.